LANGUAGE USE AS A PART OF CHARACTER VALUES - Jusuf, Harni (Institut Agama Islam Negeri, 2014)
As the social men people interact each other whether in family life and society life through communication, both verbal and non-verbal communication. To communicate, people use language to convey their feeling, thought, and intention. The used language can be formal or informal. Because of that, communication ability is very important since the used language to communicate shows the character of language user.Â Sebagai makhluk sosial manusia berinteraksi dengan sesamanya baik di lingkungan keluarga maupun di lingkungan masyarakat melalui komunikasi, baik komunikasi verbal dan non-verbal. Untuk berkomunikasi manusia menggunakan bahasa untuk menyampaikan maksud mereka. Bahasa yang digunakan pun bisa bersifat resmi dan tidak resmi. Oleh sebab itu kemampuan berkomunikasi sangatlah penting karena bahasa yang digunakan untuk berkomunikasi menunjukkan karakter pengguna bahasa tersebut.Â